Farmers’ demand for quality and nutritionally enhanced sweetpotato planting material: Evidence from experimental auctions in Rwanda - Okumu, O.O.; Rajendran, S.; Okello, J.J.; Ward, Patrick S.; Gatto, M.; Kilwinger, Fleur B.M.; Maredia, M.; Kirimi, S.; Nshimiyimana, J.C.; Ndirigwe, J.; Uzamuschaka, S.; Munyabarame, D.; et al. (International Potato Center, 2021)
Most farmers source sweetpotato vines from neighboring farmers or from cuttings taken from their own plots during the previous season. In the absence of “clean” vines prepared with more attentive production practices, farmer-to-farmer vine exchanges and own-saved vines tends to encourage the accumulation of pests and diseases that ultimately affect yields. In addition, the perishability and bulkiness of its primary propagation material – vines – there is relatively little articulated demand for vines through either market or non-market exchanges. In addition, demand for nutritionally rich variety and biofortified crop orange-fleshed sweetpotato (OFSP) is limited because of multiple factors including farmers’ unfamiliarity with the product and its novel attributes such as its high beta carotene content, the search costs incurred in locating the product, and information asymmetries between buyer and seller about the quality and performance of the product. We investigate demand for quality vine and nutritional attribute of the crop using a second price experimental auction approach by determine the premium price farmers are willing to pay for these attributes and investigate drivers of demand. In the absence of information on the source of vines, maturity and resistance to diseases, farmers are willing to pay a premium of about 35 Rwandan Francs for high quality vines sourced from decentralized vine multipliers. However, on provision of information on the source of vines, maturity and resistance to diseases of the vines, the premium price increases significantly to 133.71 Rwandan francs and to 107.22 Rwandan Francs after provision of visual information depicting the performance of the vines in demonstration plots. The premium price also increases significantly for vines sourced from neighbors to about 74.35 Rwandan francs, which further increases to 151.53 Rwandan francs when nutrition information is provided to the farmers. The study also revealed that demand for high quality vines is correlated with sex of household head, sex of the respondent, age of the respondent in years, household size, membership in a farmer organization, information from neighbors/other farmers, access to marshland, females make agriculture decisions in the household among other factors. In terms of policy, there is need to promote importance of quality vine and nutritional value of OFSP through sensitization on the field demonstration and nutritional values.